Honoring Motherhood: The Meaning of Childbirth for Tongan Women. Issue 3 (May 2017) - Reed, Shelly J.; Callister, Lynn Clark; Kavaefiafi, 'Ana; Corbett, Cheryl; Edmunds, Debra
Abstract: Purpose: The purpose of this ethnographic study was to describe the meaning of childbirth for Tongan women. Study Design and Methods: In this qualitative descriptive study, 38 Tongan women, 18 from Tonga and 20 from the United States, who had given birth in the past year were invited to share their perceptions of childbirth. Themes were generated collaboratively by the research team. Findings: The overarching theme was honoring motherhood; other themes include using strength to facilitate an unmedicated vaginal birth, describing the spiritual dimensions of birth, adhering to cultural practices associated with childbearing, and the influence of the concept of respect on childbearing. Implications for Clinical Practice: Understanding the value Tongan women and their families place on motherhood can help nurses to give culturally sensitive nursing care. Tongan beliefs and cultural practices should be respected. Nurses should assess women's personal preferences for their care and advocate for them as needed. Sensitivity to stoicism is important, especially on pain control and patient education. Nurses should be aware of Tongan values regarding modesty and respect, and provide an appropriate care environment. A culturally competent nurse understands the importance of sociocultural influences on women's health beliefs and behaviors and generates appropriate interventions. Abstract : Tongan women who had recently given birth were intereviewed about their experiences in this study. The overarching theme was honoring motherhood, with other subthemes related to an unmedicated vaginal birth, spiritual dimensions of birth, cultural practices, and the concept of respect. These data will be useful for nurses caring for women from Tonga who are giving birth in the United States.